A Novel pH-Sensitive Multifunctional DNA Nanomedicine: An Enhanced and Harmless GD2 Aptamer-Mediated Strategy for Guiding Neuroblastoma Antitumor Therapy - Zhang L (International Journal of Nanomedicine, 2021)
Liyu Zhang,1,2 Meng Wang,3 Zeen Zhu,4 Chenxi Ding,1 Shengquan Chen,1 Haibin Wu,2 Ying Yang,2 Fengyu Che,2 Qiao Li,5 Hui Li1,6 1Department of Neonatology, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China; 2Shaanxi Institute of Pediatric Diseases, Affiliated Children’s Hospital of Xi’an Jiaotong University, Xi’an, People’s Republic of China; 3Department of Emergency Surgery, Shaanxi Provincial People’s Hospital, Xi’an, Shaanxi, People’s Republic of China; 4Department of Hepatobiliary Surgery, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi 710061, People’s Republic of China; 5Department of Clinical Laboratory, Affiliated Children’s Hospital of Xi’an Jiaotong University, Xi’an, People’s Republic of China; 6Department of Neonatology, Affiliated Children’s Hospital of Xi’an Jiaotong University, Xi’an, People’s Republic of ChinaCorrespondence: Hui LiDepartment of Neonatology, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of ChinaEmail huili@xjtu.edu.cnBackground: GD2 is a mainstream biomarker for neuroblastoma (NB)-targeted therapy. Current anti-GD2 therapeutics exhibit several side effects since GD2 is also expressed at low levels on normal cells. Thus, current anti-GD2 therapeutics can be compromised by the coexistence of the target receptor on both cancer cells and normal cells.Propose: Aptamers are promising and invaluable molecular tools. Because of the pH difference between tumor and normal cells, in this study, we constructed a pH-sensitive aptamer-mediated drug delivery system (IGD-Targeted).Methods: In vivo Systematic Evolution of Ligands by Exponential Enrichment (SELEX) was used to generate a novel GD2 aptamer. Flow cytometry and molecular docking were applied to assess the binding specificities, affinities abilities of the aptamers. Confocal microscope, CCK8 assay, and BrdU assay were utilized to evaluate whether IGD-Targeted could only bind with GD2 at acidic environment. To evaluate whether IGD-Targeted could inhibit GD2-positive tumor and protect normal cells, in vivo living imaging, histomorphological staining, blood test, and RNA-sequencing were observed in animal model.Results: GD2 aptamer termed as DB67 could bind with GD2-positive cells with high specificity, while has minimal cross-reactivities to other negative cells. It has been validated that the i-motif in IGD-Targeted facilitates the binding specificity and affinity of the GD2 aptamer to GD2-positive NB tumor cells but does not interfere with GD2-positive normal cells at the pH of the cellular microenvironment. In addition, IGD-Targeted is capable of delivering Dox to only GD2-positive NB tumor cells and not to normal cells in vivo and in vitro, resulting in precise inhibition of tumor cells and protection of normal cells.Conclusion: This study suggests that IGD-Targeted as a promising platform for NB therapy which could show greater tumor inhibition and fewer side effects to normal cells, regardless of the existence of the same receptor on the target and nontarget cells.Keywords: neuroblastoma, GD2 aptamer, pH-sensitive, i-motif, antitumor therapy